Culturally and linguistically diverse mothers accessing public health nursing: A narrative review. Issue 1 (22nd November 2021) - Bonakdar Tehrani, Mehrnoush; Kemp, Lynn; Baird, Kelly
Abstract: Background: Culturally and linguistically diverse (CALD) families with young children are less likely to seek out healthcare services in comparison with the mainstream population. A lack of appropriate access and engagement with public health nursing (PHN) service contributes to major health disparities for CALD mothers. Aim: To describe and synthesize the available literature on the factors that promote or hinder CALD mothers' access to and engagement with PHN services and in particular sustained nurse home‐visiting (SNHV) programs. This paper identifies gaps and new areas of needed research inquiry to support best provision of PHN for CALD mothers. Method: A narrative review of the literature was conducted. Databases searched included PubMed, CINAHL, MEDLINE, Cochrane, and Scopus with year of publication between 2000 and 2020. Results: Of 463 total articles, 12 met inclusion criteria. The key barriers and facilitators identified were grouped in three major themes. These include mother‐related issues, experiences with interpreters, and program and program delivery related issues. Discussion: The review demonstrates that CALD mothers with limited English proficiency (LEP) are experiencing multiple challenges in accessing and engaging with PHN and SNHV services. More research is needed to understand nurse‐mother‐interpreter relationships and policy and practice issues.